Vaginal Progesterone Prophylaxis for Preterm Birth (the OPPTIMUM Study): A Multicentre, Randomized, Double-Blind Trial. Issue 9 (September 2016) - Norman, Jane Elizabeth; Marlow, Neil; Messow, Claudia-Martina; Shennan, Andrew; Bennett, Phillip R.; Thornton, Steven; Robson, Stephen C.; McConnachie, Alex; Petrou, Stavros; Sebire, Neil J.; Lavender, Tina; Whyte, Sonia; et al.
Abstract : (Abstracted from Lancet 2016;387:2106–2116) Administration of vaginal progesterone or intramuscular 17α-hydroxyprogesterone caproate has been found to prevent preterm birth in women with a short cervix and to reduce neonatal mortality as reported by the Cochrane Library meta-analysis. However, data on medium and long-term outcomes after the neonatal period are lacking.